Detailed breast cancer pathology data for large-scale studies - access and completeness in NSW, Australia - Mark J Bartlett; Valerie Beral; Xenia Dolja-Gore; Toral Gathani; Bette Liu (Sax Institute, 2021)
Objectives: We sought to determine the ease with which breast cancer pathology data could be ascertained for a large cohort of Australian women, to support epidemiological research. Method: We assessed a range of options for accessing breast cancer pathology data. Manual review of the pathology report provided to the New South Wales Cancer Registry (NSWCR) was considered most feasible, complete and reliable. Incident breast cancers (ICD-10 C50) in female 45 and Up Study participants, resident in NSW, were identified from linked NSWCR data for the period 2006-2012. Data not routinely available in the NSWCR, including hormone receptor status, were extracted from the pathology report provided to the registry. Results: Among 143 079 eligible women, 2051 had a first registration of breast cancer following cohort recruitment. The mean age at cancer diagnosis was 64.5 years. Based on cancer registry data, the cancers were predominantly ductal (74.1%), 54.4% were localised to the breast at diagnosis and 24.2% were >50 mm in size. Based on manually extracted data from pathology records, 23.9% of cancers were histological grade 1, 79.6% were oestrogen receptor positive and 71.2% were progestogen receptor positive. These data were mostly complete (<10% missing). HER2 receptor status was less well reported, with 31.9% of cancers having indeterminate or missing data, while 11.3% were reported as positive. Data on lymph node status was missing in 16.1% of breast cancer reports, 33.7% were node positive. 8.0% of breast cancers had involved surgical margins, and this data was missing for 14.1% of cases. Conclusion: Pathology information, in addition to that available from routine registry data, is required both for breast cancer research and for monitoring trends in the types of breast cancer occurring over time in Australia. All the important additional data items required are recorded on the pathology report, which is provided to the NSWCR as part of cancer notification but is not routinely coded, and are generally fairly complete. However, access to these data for large-scale studies requires substantial effort. Coding the pathology data and making it routinely available would substantially improve cancer research and enable proper monitoring of breast cancer trends in Australia.